The strategy of urban life : reinventing practice in the disenchanted world : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Social Anthropology at Massey University - Mahar, Cheleen (Massey University, 1987)
The economic practice of a Mexican squatter settlement provides the focus for this study. The thesis argues that traditional structures of individual and community have been transformed in squatter settlements to function as economic structures influenced by the logic of capitalism. Using a method deriving from Bourdieu's ethnographic account of field, habitus and strategy, the varied and complex struggles for economic and social survival among Oaxacan squatter residents are examined. It is contended that a method which overcomes the idealist limitations of interactionist theory, and the structuralist limitations of functionalist theory, as well as the determinism of marxist theory is necessary. Using Bourdieu's method, a dialectical analysis examines the forms of capital, the struggles for position, and the economic practices in the fields of economics, social relations and community politics. The study concludes with a critique of the method.
Keywords: Squatter settlements; Mexico; Pierre Bourdieu; Oaxaca; Economic theory